Chemical environment and occupation sites of hydrogen in LiMO3. Issue 2 (13th December 2022) - Köhler, Thomas; Zschornak, Matthias; Röder, Christian; Hanzig, Juliane; Gärtner, Günter; Leisegang, Tilmann; Mehner, Erik; Stöcker, Hartmut; Meyer, Dirk C.
Abstract : A description of the hydrogen occupation site in LiNbO3 and LiTaO3 is made based on theoretical structural models and validated by measured OH − stretching vibrational modes. Abstract : It is well known that LiMO3 crystals contain a natural hydrogen defect, which binds to oxygen and forms OH − defects. Since the shape of the corresponding absorption band varies strongly depending on the crystal stoichiometry, we can use it to elucidate the existence of different hydrogen occupation sites and the associated chemical environment. For this purpose, FT-IR and Raman spectra of the OH − stretching vibration are measured on a set of near-stoichiometric and congruent LiNbO3 and LiTaO3 crystals. Density functional theory and bond valence energy landscape calculations lead to the same result that ideal stoichiometric LiMO3 structures feature two stable hydrogen sites. The two configurations are located on the O–O connection line between two oxygen planes forming a regularly empty octahedron. In contrast to the theoretical calculations, it can be concluded from the experimental FT-IR spectra of near-stoichiometric and congruent material that the OH − defect is almost completely located within the O–O plane perpendicular to the crystallographic c axis. We will show that intrinsic and extrinsic defects are responsible for this positioning of the hydrogen in the O–O plane. The extrinsic defects are paramagnetic impurities decorated with hydrogen. They are responsible for the narrow and dominant sub-band component at ∼3460 cm −1 in near-stoichiometric crystals. The congruent materials have a high intrinsic defect cluster density and especially lithium vacancies are preferentially decorated by hydrogen. These defect sites are assigned to the other sub-band components found in congruent LiMO3 crystals.